PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI SELAMA PANDEMI: SEBERAPA BESAR PENGARUH LITERASI EKONOMI DAN KONTROL DIRI ? - Rahayu Putri Prasanti; Putri Ulfa Kamalia (STKIP Persada Khatulistiwa Sintang, 2022)
The problem discussed in this study is the high consumptive behavior of students during the pandemic. This study aims to analyze the effect of economic literacy and self-control on the consumptive behavior of UNESA Economic Education Study Program students during the pandemic. The research method used is correlational research using a quantitative approach. The data was obtained from students of the 2018-2021 Economic Education Study Program and a sample of 73 students was obtained as the primary source. Data were collected using a questionnaire method. From the results of data processing carried out, the results obtained which state that the variables of economic literacy and self-control partially or simultaneously have a significant influence on the consumptive behavior of students of the UNESA Economic Education Study Program. This is in accordance with the conditions that occur in the field that consumptive behavior carried out by students is influenced by economic literacy and self-control